Sanksi Hukum Terhadap Pelaku Tindak Kekerasan Terhadap Perempuan dan Anak - Taufiq Taufiq (Faculty of Law, Universitas Pekalongan, 2020)
Violence against women and children is any act that results in physical and psychological suffering for women and children. Violence against women and children is a crime that can be subject to criminal sanctions. The government tries its best to eradicate and eliminate acts of violence against women and children, by enacting Law Number 23 of 2002 as amended by Law Number: 35 of 2014 concerning the first amendment to Law Number 23 of 2002 concerning child protection , which was amended again by Perpu Number: 1 of 2016 concerning the third amendment of Law Number: 23 of 2002 concerning child protection, and Law Number: 23 of 2004 concerning the Elimination of domestic violence. The provisions of the laws and regulations as mentioned above, although they contain heavy legal sanctions, in reality there are still many cases of violence against women and children. This study uses a normative juridical approach or library research. The conclusion from the research results is that heavy legal sanctions, without ethical awareness of law enforcement officials to commit to enforcing them, will not deter the perpetrators and others from committing acts of violence against women and children. Eradicating or eliminating violence against women and children requires comprehensive efforts from all components of the nation, starting with taking formal and non-formal preventive actions.Keywords:Legal; Sanctions; Violence